REVITALISASI WAKAF UNTUK KEMASLAHATAN UMAT - Lestari, Ana Indah (ZISWAF, 2017)
Islam as a perfect teaching places the position of waqf as a very important instrument of society. The use of waqf as one of the resources used by the Muslim community has made progress now. This is evident from the increasing number of waqf assets in Indonesia. Aside from being a source of funding for social, educational and health activities, waqf can also be used as an alternative to empower the people>s economy as the main pillar of the welfare of the ummah, so that the benefits are sustainable. With the concept of waqf revitalization, it is expected to be able to support to improve the empowerment of waqf for the benefit of the ummah. Revitalization of waqf is not only able to give positive impact that can be felt directly but also indirectly able to form a professional waqf management capable of developing waqf so that waqf can become the strengthening of prosperity of the people.